If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 1 = 5x + 49 Reorder the terms: 1 + 13x = 5x + 49 Reorder the terms: 1 + 13x = 49 + 5x Solving 1 + 13x = 49 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 1 + 13x + -5x = 49 + 5x + -5x Combine like terms: 13x + -5x = 8x 1 + 8x = 49 + 5x + -5x Combine like terms: 5x + -5x = 0 1 + 8x = 49 + 0 1 + 8x = 49 Add '-1' to each side of the equation. 1 + -1 + 8x = 49 + -1 Combine like terms: 1 + -1 = 0 0 + 8x = 49 + -1 8x = 49 + -1 Combine like terms: 49 + -1 = 48 8x = 48 Divide each side by '8'. x = 6 Simplifying x = 6
| 97+13m=5+17m | | 8y^2-y=-9 | | 11x=3x-56 | | 3x+9-7x=33 | | 5-y=10y-40 | | -3=4(-3)+6-(-3) | | 141000000/1.17 | | 6x+2-3x+2=9x-12 | | 9-5/3b=3 | | 2x^2-8x+8=98 | | 5(2+X)=3x-4 | | x^2/4x | | u^2-10u-21=0 | | 2x+4/3=x/7 | | 10+10M=0.35M | | 3m+71=11m+15 | | (u^2-8u-12)2=0 | | 14m+6=9m+91 | | 26x^2-30x-1147=0 | | 5-(2x-3)=-3+6 | | 9/30 | | 183-2m=4m | | 4X-3/5=X+3/10 | | X^2-10x+7=3 | | 135+4m=13m | | 7/8=5/8+9 | | 4X-3/5 | | 8m+78=11m | | 5-x+3x=29 | | 7-6(5y-y)=10(y-4) | | 12m=7m+205 | | -4c=28 |